Non-Diffractive Nuclear Excitations In Angantyr - Rosenkvist,Carl (2023)
To better understand collectivity in high energy physics, the heavy-ion collision model Angantyr was developed to be included in the event generator Pythia. In this model, proton-proton collision phenomenology is extrapolated to heavy-ion collisions without assuming a thermal plasma for particle production. Hence, this model may help disentangle possible thermal and non-thermal phenomena contributing to collective effects. In Angatyr, nucleons which are already wounded may interact further in secondary interactions analogous to that of multiple parton interactions. There are several different interactions, but the most important one is the interaction involving color exchange, which is referred to as absorptive interactions. Due to technical challenges, secondary absorptive interactions have been simulated by using modified single diffraction events. In this thesis, we explore the possibility and result of simulating secondary absorptive interactions as modified inelastic non-diffractive events instead. This change required considerations of color flow between the interacting nucleons, energy-momentum conservation, and invariant mass distribution of the secondary event. Furthermore, we also investigated different possibilities of using the new method.
Keywords: Heavy-ion; non-diffractive; nuclear excitation; secondary interactions